Brand-Trust Enhancing Sales Promotion through Online Shopping - Arsil Imawan; Ayu Ekasari (International Journal of Digital Entrepreneurship and Business, 2020)
The research aims to determine the effects of sales promotion on online shopping moderated by brand trust. Meanwhile, data was directly collected through the distribution of questionnaires to 210 respondents. The sample was obtain using a purposive sampling technique. Furthermore, the hypotheses were tested using SEM analysis (Structural Equation Model). The results confirmed that the influence of sales promotion on shopping is moderated by brand trust. It also confirmed that the brand trust is a variable model that moderates the effect of sales promotion. Therefore, this study has implications for online retail managers in creating trust among consumers.